Activation of Human Neutrophils by the Anti-Inflammatory Mediator Esenbeckia leiocarpa Leads to Atypical Apoptosis - Rafael de Liz; Heros Horst; Moacir Geraldo Pizzolatti; Tânia Silvia Fröde; Denis Girard (Mediators of Inflammation)
Despite the fact that Esenbeckia leiocarpa, a Brazilian plant, possesses potential anti-inflammatory properties, its effect in neutrophils, key players in inflammation, has never been investigated. In this study, a crude hydroalcoholic extract (CHE) was used to evaluate the potential toxic or agonistic effect of E. leiocarpa in human neutrophils. At a noncytotoxic concentration of 500 μg/mL, CHE increased actin polymerization and cell signaling events, especially p38 MAPK. Its modulatory activity on neutrophil cell apoptosis was investigated by cytology and by flow cytometry and, although CHE increased the apoptotic rate (by cytology) and increased annexin-V binding, it did not, unexpectedly, increase CD16 shedding. CHE increased the degradation of the cytoskeletal proteins gelsolin and paxillin but, surprisingly, not of vimentin. The proapoptotic activity of CHE was reversed by a pan-caspase inhibitor but not by a p38 inhibitor. We conclude that CHE is a novel human neutrophil agonist that induces apoptosis by a caspase-dependent and p38-independent mechanism in an atypical fashion based on its lack of effect on CD16 shedding and vimentin degradation. Since the resolution of inflammation occurs by elimination of apoptotic neutrophils, the ability of CHE to induce neutrophil apoptosis correlates well with its anti-inflammatory properties, as previously reported.